Candida Endocarditis in a Hemodialysis Patient - Kishalay Mahajan; Pratik Tripathi; Gaurav Kumar Khandelwal; Shaurya Mehta; Manna Bhattacharjee (APIK Journal of Internal Medicine)
Fungal endocarditis in hemodialysis patient is a rare and extremely debilitating disease associated with high morbidity and mortality. The 2009 Infectious Diseases Society of America guidelines suggest the combined use of surgery and antibiotics to treat candidiasis; whereas, successful nonsurgical treatment of Candida endocarditis has been reported. Case Presentation: A patient with chronic kidney disease was admitted to the Intensive Care Unit (ICU) after experiencing fever with shortness of breath for last 15days and swelling of whole body for 1 week. Blood culture revealed Candida albicans infection. On further workup he was found to have infective endocarditis with a large vegetation across the tricuspid valve. He was treated with intravenous and oral antifungal therapy for eight weeks. Valvular surgery was not performed. The patient clinically improved. Central venous catheters and AV fistulae are major sources of infection. Strict adherence to hygiene rules and prevention guidelines are mandatory in hemodialysis patients to prevent infectious complications.